Rancangan dan Implementasi Learning Managements System Berbasis Web (Studi Kasus: SMA Nahdhotul Islam Sri Tiga) - Nurul Huda; Kasino Kasino (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
The use of technology in the era of the COVID-19 virus is increasingly demanded to be used throughout the world. The impact of changes that are seen very clearly in this era of covid 19 is in the field of education. Where previously the education system was still running normally with face to face, turned into distance learning (online). To support distance learning, a technology in the field of education is needed, one of which is a learning management system (LMS) such as e-learning that can be used in these conditions. SMA Nahdhotul Islam Sri Tiga is an official high school education, this school has quite qualified learning and educational facilities such as a computer lab and a fairly good internet connection. However, even in this era of covid 19, the teaching and learning process activities used in online learning are not optimal. Therefore, to overcome this problem, an e-learning system is designed that can assist in the distance learning process at SMA Nahdhotul Islam Sri Tiga more effectively and make it easier for teachers to distribute materials and students to receive materials. The system development method used for the design is the Prototype method. The prototype method is one of the new methods in the cycle of information system development, not only from existing information system development methods, but also as a flow in system development where system development and users can experiment from the initial development process. In the prototype method there are 3 stages in system development, namely the communication stage, the design stage and the testing stage.